Elastic behaviour analysis of multi-layered composite beams with asymmetrical depth-wise material variation under pure tension [electronic resource] - Gholamali Sharifishourabi, 1979-; Amran Ayob, supervisor; Mohd. Yazid Yahya; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2014